The Diagnostic and Therapeutic Role of Leptin and Its Receptor ObR in Glioblastoma Multiforme - Kinfe, Thomas Mehari; Stadlbauer, Andreas; Bozhkov, Yavor; Kremenevski, Natalia; Brandner, Sebastian; Buchfelder, Michael; Chaudhry, Shafqat R. (Cancers, 2020)
Simple Summary
CRIS-Team WoS Importer:2021-01-08